Häufigkeit und Vorkommen multiresistenter gramnegativer Erreger: 3MRGN/4MRGN - Hamprecht, Axel G.; Göttig, Stephan (DMW - Deutsche Medizinische Wochenschrift, 2018)
The increase of multidrug-resistant Gram-negative bacilli (MRGN) is a great threat for both the health system and patients. Challenges of MRGN for physicians are limited therapeutic options, the need of infection control measures and the danger of outbreaks. In this article, the prevalence of MRGN, risk factors, the background and definitions of multidrug-resistant organisms are presented.
Keywords: ESBL; Carbapenemase; MRGN; MRGN; CPE; CRE